RANCANGAN PERCOBAAN INFRARED THERMOMETER: KALIBRASI DAN KEUNGGULAN PEMANFAATANNYA - Sutrisnawati - Mehora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
His experiment aims to determine whether the reading of the infrared thermometer depends on the distance or angle of the incident ray, know the calibration and validation of the infrared thermometer and determine the temperature as a function of position and time for 1-D and 2-D objects and analyze the measurement results. The first experiment was carried out on objects with different areas, namely walls and small aluminum slabs with a size of 3.8cm x 3.8cm. The second experiment was also conducted on different objects, namely water with a temperature of 30oC and 60oC, which was measured at the same temperature using an infrared thermometer and an alcohol thermometer. The third experiment was carried out on 1D objects with 2 different types of materials and one type of 2D material. From the results of the experiment it can be concluded several things, for experiment one obtained differences in the reading of the thermometer at various angles and distances for object 2 (small plates), while for objects with large areas such as thermometer reading walls remain the same for different distances and angles. The thermal conductivity coefficient of aluminum is greater than iron.